Intermittent loss of consciousness during cesarean section under spinal anesthesia: a case report - Kayaalti,Selda (2019)
Abstract Loss of consciousness during spinal anesthesia is a rare but scary complication. This complication is generally related to severe hypotension and bradycardia, but in this case, the loss of consciousness occurred in a hemodynamically stable parturient patient. We present a 31 years-old patient who underwent an emergency cesarean section. She lost consciousness and had apnea that started 10 minutes after successful spinal anesthesia and repeated three times for a total of 25 minutes, despite the stable hemodynamics of the patient. The case was considered a subdural block, and the patient was provided with respiratory support. The subdural block is expected to start slowly (approximately 15-20 minutes), but in this case, after about 10 minutes of receiving anesthesia, the patient suddenly had a loss of consciousness. After the recovery of consciousness and return of spontaneous respiration, the level of a sensory block of the patient, who was cooperative and oriented, was T4. There were motor blocks in both lower extremities. Four hours after intrathecal injection, both the sensory and motor blocks ended, and she was discharged two days later with no complications. Hence, patients who receive spinal anesthesia should be closely observed for any such undesirable complications.